What have we Learned from Firm Efficiency Research for the Past 35 Years? A Bibliometric Analysis - Mustaffa, Abd Hadi; Bahrudin, Nur Zahidah; Sahudin, Zahariah; Abdullah, Hasni; Abdul Aziz, Muhammad Ridzuan (Information Management and Business Review, 2023)
The increasing publication and citation performances of Firm Efficiency research for the past 35 years have attracted scholars to further embark on this area. Hence, the main objective of this study is to explore what scholars have learned from Firm Efficiency research over the past 35 years. This study uses bibliometric analysis to analyze top productive countries, top 10 journals, top 10 prominent authors, top 20 cited articles, and emerging themes. Selected findings indicated that the United States, China and Taiwan are the top three most productive countries in Firm Efficiency research. In addition, five emerging themes were highlighted in Firm Efficiency research for the past 35 years. The five themes were: 1) Stochastic Frontier Analysis in measuring firm productivity and size, 2) Bootstrapping DEA and SFA in measuring firm efficiency, 3) Corporate Governance and Technical Efficiency, 4) DEA as benchmarking in Firm Efficiency, and 5) Capital Structure and Ownership Structure. This study provides three contributions – 1) encourage scholars to observe the trends in publication and citation performances. 2) Allow scholars and authors to collaborate with an expert in Firm Efficiency research in the future, and 3) inspire the authors to look at the potential research gap and future directions in Firm Efficiency research.